The technology of synthetic environment constructing for information security systems - Казимир, В.В.; Сіра, Г.А.; Черних, Д.О. (Proceedings of National Aviation University (archive), 2010)
An information technology is suggested to provide the automatic development of simulated models by converting graphic models of business process, got by other programs for modeling. Got simulated models can be used for the synthetic environment construction of information security systems to define more exactly models features and characteristics. Developed information technology can be as base for distributed modeling systems constructing within the limits of realization HLA.